Amphiphilic tocopheryl polyethylene glycol succinate as gas chromatographic stationary phase for high‐resolution separations of challenging isomers and analysis of lavender essential oil. Issue 19 (10th August 2021) - Zhao, Huiru; Qi, Meiling
Abstract: This work presents the investigation of using tocopheryl polyethylene glycol succinate as the stationary phase for gas chromatography separations of isomers with different varieties and gas chromatography‐mass spectrometry analysis of a wide range of components in lavender essential oil. Its capillary column exhibited moderate polarity and column efficiency of 4000 plates/m determined by n ‐dodecane at 120°C. As demonstrated, it showed outstanding separation performance toward challenging isomers such as xylenes, alkanes, phenols, and anilines and a wide range of components in essential oils with distinct advantages over the commercial polyethylene glycol and polysiloxane columns. Moreover, its capillary columns displayed excellent repeatability and reproducibility with the RSD values of the retention times in the range of 0.02–0.07% for run‐to‐run, 0.14–0.22% for day‐to‐day, and 2.5–4.3% for column‐to‐column. Its application to gas chromatography‐mass spectrometry analysis of the lavender essential oil proved its good potential for practical gas chromatography analyses. To our knowledge, this work presents the first example of employing tocopheryl polyethylene glycol succinate for chromatographic analyses and demonstrates its promising future in this field.